Implementasi Software Solidworks dalam Perancangan Produksi Lemari untuk Efisiensi Waktu Produksi - Prasetyo, Ahmad; Sihole, Asep Tiroy Pardamean; Khairunisa, Meutia Dwina; Najibbulloh, Muhammad; Atmayati, RAhmita (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The design of furniture products, such as cabinets, requires precision and considerable time, especially in the design and prototyping stages. With the development of technology, the use of computer-aided design (CAD) software such as Solidworks is a solution to improve efficiency in product design. This journal discusses the implementation of Solidworks in cabinet planning, with a focus on reducing production time and improving design accuracy. Through the use of Solidworks, the design process can be digitized, allowing designers to create more accurate and easily modifiable 3D models, and reducing errors that often occur in manual design. In addition, the simulation and analysis features in Solidworks also facilitate the identification of problems before the production stage begins, thereby reducing the risk of errors in the manufacture of cabinets. The results of this software application show that the time required to design cabinets can be significantly reduced, by increasing the efficiency of production time, reducing material waste, and accelerating prototyping. Therefore, the use of Solidworks is very effective in improving time efficiency and product quality in the furniture industry.